An improved theoretical formulation for Sauter mean diameter of pressure-swirl atomizers using geometrical parameters of atomization - Ronceros Rivas, Julio R. (2022)
This study discusses the development of a mathematical model that is capable of predicting the drop size mean diameter of the spray generated by a pressure swirl atomizer, considering the effects of the liquid's viscosity and the geometrical parameters of this type of injector, as well as the angle of incidence of the inlet channels (ψ and β) and atomization parameters (k, ϰ), obtained from hyperbolic relations. Additionally, this model investigates the phenomena of rupture and stability that are observed in the conical liquid film, in which the importance of a new geometrical parameter of atomization, “ϰ”, which immediately influences the drop size diameter of the spray, should be highlighted. The results that are obtained using this model are compared with analytical results of Couto, Wang and Lefebvre, Jasuja, Radcliffe and Lefebvre, experimental results and numerics (Hollow cone atomization model), using the Ansys Fluent software for the validation and consistency of the model proposed in Rivas (2015). This model yields good approximations as compared to that yielded using other alternative mathematical models, demonstrating that the new atomization geometric parameter “ϰ” is an “adjustment” factor that exhibits considerable significance while designing pressure swirl atomizers according to the required SMD. Furthermore, this model is easy to use, with reliable results, and has the advantage of saving computational time.